2006
DOI: 10.1039/b514889h
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3 adducts of transition metal acyl compounds

Abstract: The transition metal acyl compounds [Co(L)(CO)3(COMe)] (L = PMe3, PPhMe2, P(4-Me-C6H4)3, PPh3 and P(4-F-C6H4)3), [Mn(CO)5(COMe)] and [Mo(PPh3)(eta(5)-C5H5)(CO)2(COMe)] react with B(C6F5)3 to form the adducts [Co(L)(CO)3(C{OB(C6F5)3}Me)] (L = PMe3, 1, PPhMe2, 2, P(4-Me-C6H4)3, 3, PPh3, 4, P(4-F-C6H4)3), 5, [Mn(CO)5(C{OB(C6F5)3}Me)] 6 and [Mo(eta(5)-C5H5)(PPh3)(CO)2(C{OB(C6F5)3}Me)], 7. Addition of B(C6F5)3 to a cooled solution of [Mo(eta(5)-C5H5)(CO)3(Me)], under an atmosphere of CO gave [Mo(eta(5)-C5H5)(CO)3(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…At 40 ppm in the 11 B NMR spectrum of the wetted BCF‐impregnated polyamine there is an additional small peak. The BCF itself has a chemical shift of 65–59 ppm (in CD 2 Cl 2 /C 6 D 6 , CD 2 Cl 2 , C 6 D 6 , CDCl 3 ) . Because of this, it is hypothesized that this signal results from the appearance of a borane species with less interaction with the polymer when the solvent is added.…”
Section: Resultsmentioning
confidence: 99%
“…At 40 ppm in the 11 B NMR spectrum of the wetted BCF‐impregnated polyamine there is an additional small peak. The BCF itself has a chemical shift of 65–59 ppm (in CD 2 Cl 2 /C 6 D 6 , CD 2 Cl 2 , C 6 D 6 , CDCl 3 ) . Because of this, it is hypothesized that this signal results from the appearance of a borane species with less interaction with the polymer when the solvent is added.…”
Section: Resultsmentioning
confidence: 99%
“…The 11 B{ 1 H} NMR signal is relatively sharp and in a range as expected for fourcoordinate boron, formed by internal N À B interaction ( 11 B{ 1 H}: d = + + 4.6 ppm). [13,14] The carbocyclic five-mem- (d, 3 J P-C = 15.3 Hz)), respectively. The X-ray crystal structure analysis of 9 (see Figure 1) confirms that the B À C s bond of the reagent 1 was cleaved during the reaction and that the resulting À BA C H T U N G T R E N N U N G (C 6 F 5 ) 2 and À CH 2 CH 2 À PMes 2 components were added to the adjacent former fulvene ring carbon atoms (C1 and C8, see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…X-ray crystal structure analysis of 13: Formula C 21 H14 BF 10 N, M = 481.14, light yellow crystal 0.17 0.15 0.15 mm, a = 15.1034(3), b = 15.6593(4), c = 16.4607(4) , V = 3893.10(16) 3 , 1 calc = 1.642 g cm À3 , m = 1.457 mm À1 , empirical absorption correction (0.790 T 0.811), Z = 8, orthorhombic, space group Pbca (No. 61), l = 1.54178 , T = 223(2) K, w and f scans, 27 558 reflections collected (AE h, AE k, AE l), [(sinq)/l] = 0.60 À1 , 3376 independent (R int = 0.093) and 2342 observed reflections [I !…”
mentioning
confidence: 99%
“…The use of B(C 6 F 5 ) 3 as a catalyst for CO induced migratory insertion has also been reported. 71 The stereochemistry of mono-and bis-B(C 6 F 5 ) 3 -benzotriazole adducts have been investigated by variable temperature 19 F-NMR spectroscopy and X-ray crystallography. 72 The reaction of B(C 6 F 5 ) 3 with 7-azaindole has been investigated, and the competitive coordination of the azaindole, pyrole and indole adducts with pyridine investigated using NMR spectroscopy.…”
Section: Boryl Complexes and Related Systemsmentioning
confidence: 99%
“…197 The possibility that the general lack of common octahedral Ga hydride structures might be a property endemic to gallium itself, was considered. 198 A helpful study describing the solid-state NMR characteristics of both 69 Ga and 71 Ga was reported. 199 Two binary compounds, Rh 4 Ga 21 and Rh 3 Ga 16 , represent new structure types for intermetallic compounds, and are best described using the intergrowth structure concept.…”
Section: General or Fundamentalmentioning
confidence: 99%